Investigação de algumas atividades biológicas da peçonha da serpenteMicrurus lemniscatus (Linnaeus, 1758) - Thiago Geraldo Soares (2015)
The study of snake venoms is useful to development of therapies against snakebites and these venoms are also source of molecules with therapeutic potential. Therefore it can be used as prototypes for the development of drugs and other biotechnological products. In this context, we performed a partial biochemical characterization and investigated some biological activities of M. lemniscatus venom and its fractionsobtained by fractionation by size exclusion (Superose 12). The fractions (EM-F1 - EM-F11) obtained were submitted to SDS-PAGE and to mass spectrometry (MALDITOF) analysis. The results showed that this venom consists mainly of components with molecular weights of 6 - 8 kDa and 12 - 14 kDa. The screening of biological activities demonstrated that the venom displayed phospholipase A2 (EM-F3 to EMF10), hyaluronidase (EM-F1 and EM-F2) and hemagglutinating (EM-F6 and EM-F7) activities and causes loss of cell adhesion in mammary adenocarcinoma in culture (EM-F1 and EM-F2). Additionally, this venom induced antimicrobial activity against Staphylococcus aureus (ATCC® 6538) (EM-F1 and EM-F2). Due to the emergence of super-resistant bacteria to commercial antibiotics and to the interest in investigating antimicrobial agents from natural sources, we isolated and characterized chemically and pharmacologically Ml-LAAO. This enzyme was purified by anion exchange chromatography (Synchropack AX300) and showed a Minimum Inhibitory Concentration (MIC) and a Minimum Bactericidal Concentration (MBC) of1.56 g/mL against Staphylococcus aureus, (ATCC® 6538). In addition, cellular toxicity of this molecule was assessed in three cell lines (THLE-2, WI-26 VA4 and HEK-293), which showed that it is not toxic for these cells, when tested at the MIC/MBC concentrations obtained against Staphylococcus aureus. Furthermore, Ml-LAAO did not cause hemolysis in rabbit erythrocytes and did not induce liposome lysis. The MALDI-TOF mass spectrometric analyses showed an apparent molecular mass of approximately 69 kDa to Ml-LAAO. Our results showed the first L-amino acid oxidase isolated from the M. lemniscatus venom. However, more studies are need to characterize the enzymatic activity of Ml-LAAO and to understand its mechanism of action in bacteria.